Beasts of Field - (:unkn) unknown (My University, 2015)
The invention of ethnozoology in West Africa between 1928 and 1960, at a time when French ethnology is professionalized and where new methodologies of fieldwork are put in place, shows the construction of unpublished knowledge, at the crossroads of ethnology and zoology. The Africanist ethnologists of the time, Marcel Griaule in the first place, have varied and often privileged relationships with animals. A certain fascination for African wildlife certainly plays a role in the scientific interest that these ethnologists develop for local zoological knowledge. To describe the ways of doing ethnozoology thus requires to take into account the ways in which ethnologists are affected by the animals concerned, through the pleasure that they maintain for hunting, their collection and capture practices or even their gestures of attachment.
Keywords: African Research